Pelaksanaan Dana Desa Di Desa Karangsalam Kidul Kecamatan Kedungbanteng Kabupaten Banyumas - Esti Ningrum; Ninik Hartariningsih (Wijayakusuma Law Review, 2020)
Abstract In order to improve services and community welfare, villages have the right to obtain Village Funds from the Central Government sourced from the State Revenue and Expenditure Budget (APBN). The condition of Karangsalam Kidul Village before receiving the Village Fund was seen in terms of facilities and infrastructure such as roads, bridges and schools which were still inadequate. Infrastructure development is hampered by limited funds owned by the village government. Under these conditions, it is difficult for Karangsalam Kidul Village to budget for development even though this is deemed important as supporting the life of the village community. The existence of the Village Fund in Karangsalam Kidul Village shows the benefits of the Village Fund for the local village community. Various Village developments have been carried out by Karangsalam Kidul Village since obtaining Village Funds from the Government. Based on the results of the interviews, the people of Karangsalam Kidul Village felt that there was a change both in terms of the economy, village facilities and infrastructure as well as from the social side.Keywords: Implementation; Village Fund.Â AbstrakDalam rangka meningkatkan pelayanan dan kesejahteraan masyarakat, Desa mempunyai hak untuk memperoleh Dana Desa dari Pemerintah Pusat yang bersumber dari Anggaran Pendapatan dan Belanja Negara ( APBN ). Kondisi Desa Karangsalam Kidul sebelum menerima Dana Desa dilihat dari sisi sarana dan prasarana seperti jalan, jembatan dan sekolah masih belum memadai. Pembangunan infrastruktur terhambat oleh keterbatasan dana yang dimiliki oleh pemerintah desa. Dalam kondisi tersebut, Desa Karangsalam kidul sulit untuk menganggarkan pembangunan meskipun hal tersebut dirasa penting sebagai penunjang kehidupan masyarakat desa. sesudah adanya Dana Desa di Desa Karangsalam Kidul menunjukkan kemanfaatan Dana Desa bagi masyarakat desa setempat. Berbagai pembangunan Desa telah dilaksanakan oleh Desa Karangsalam Kidul sejak medapatkan Dana Desa dari Pemerintah. Berdasarkan hasil wawancara, masyarakat Desa Karangsalam Kidul merasakan adanya perubahan baik dari sisi perekonomian, sarana dan prasarana desa maupun dari sisi kemasyarakatan.Kata Kunci : Pelaksanaan; Dana Desa.Â